Elevated IOP Alters the Material Properties of Sclera and Lamina Cribrosa in Monkeys. (23rd August 2022) - Jia, Xu; Zhang, Feng; Cao, Mengdan; Pan, Zheng; Liu, Ke; Zhou, Dengming; Duan, Xuanchu
Abstract : Objective . Elevated intraocular pressure (IOP) has significant impacts on different stages in the progression of chronic glaucoma. In this study, we investigated changes in the material properties of sclera and lamina cribrosa (LC) in a nonhuman primate model with elevated IOP. Methods . Normal adult Tibetan macaques were selected for the construction of elevated IOP model. After 40 days of stable maintenance on the ocular hypertension, the binocular eyeballs were obtained for the measurement of macroscopic parameters of the eyeballs. Posterior scleral tissue strips were obtained in circumferential and axial directions, and thickness was measured, respectively. Biomechanical parameters were obtained with stress relaxation, creep, and tensile test. The nanoindentation test was performed on the LC and scleral tissue around optic nerve head (ONH) to obtain compressive modulus. Results . In the presence of elevated IOP, variations of the axial diameter of the eyeball were greater than those of the transverse diameter, and the mean scleral thickness around ONH was smaller in the experimental group than control group. The elastic modulus and stress relaxation modulus of sclera were larger, and the creep rate was lower in the experimental group than control group. In the control group, the elastic modulus and stress relaxation modulus of the circumferential sclera were larger in the axial direction, and creep rate was smaller. In the experimental group, there was no significant difference in biomechanical characteristics between the two directions. Compared to the control group, the compression modulus of the LC was smaller, and the compression modulus of sclera around ONH was larger in the experimental group. Conclusion . Elevated IOP alters the viscoelasticity and anisotropy of sclera and LC. These may contribute to reduction of the organizational resistance to external forces and decline in the ability of self-recovery.